Analysis of Financial Performance (Leverage, Company Size, and Profitability) in Sharia Insurance Companies Listed on the OJK for the 2020–2022 Period - Aini, Risma Nurul; Kristianingsih, Kristianingsih (Journal of Applied Islamic Economics and Finance, 2025)
This study aims to analyze the financial performance of Islamic insurance companies in Indonesia based on leverage, company size, and profitability for the 2020–2022 period. Amidst the economic instability caused by the COVID-19 pandemic, fluctuations in profitability were observed, particularly in Return on Assets (ROA). Using the Vector Autoregressive (VAR) method, this quantitative study evaluated data from 37 Islamic insurance companies registered with the Financial Services Authority (OJK). Results revealed a short-run relationship among variables with no cointegration in the long term. Leverage and firm size significantly influence profitability, with shocks and dynamic interactions mapped through impulse response and variance decomposition analysis.